2021
DOI: 10.1016/j.jaci.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to the SARS-CoV-2 vaccine in individuals with various inborn errors of immunity

Abstract: Background SARS-CoV-2 vaccination is recommended in patients with inborn errors of immunity (IEI); however, little is known about immunogenicity and safety in these patients. Objectives To evaluate the impact of genetic diagnosis, age, and treatment on antibody response to COVID-19 vaccine and related adverse event (AE) in a cohort of patients with IEI. Methods Plasma was collected from twenty-two healthcare worker (HCW) controls, 81 IEI pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 26 publications
11
86
0
Order By: Relevance
“…The only patient who failed to have a substantial rise in post vaccination titers had a marked decrease in the frequency of circulating B cells ( 25 ). In a recent paper, a high percentage of fully immunized CVID patients developed anti-Spike IgG, at significantly lower levels than in the healthy control group ( 26 ). Our data ( 27 ) in CVID patients immunized with BNT162b2 SARS-CoV-2 mRNA vaccine contrasted with the high frequency of response reported in the cohorts illustrated above.…”
Section: Insight On Sars-cov-2mentioning
confidence: 97%
See 1 more Smart Citation
“…The only patient who failed to have a substantial rise in post vaccination titers had a marked decrease in the frequency of circulating B cells ( 25 ). In a recent paper, a high percentage of fully immunized CVID patients developed anti-Spike IgG, at significantly lower levels than in the healthy control group ( 26 ). Our data ( 27 ) in CVID patients immunized with BNT162b2 SARS-CoV-2 mRNA vaccine contrasted with the high frequency of response reported in the cohorts illustrated above.…”
Section: Insight On Sars-cov-2mentioning
confidence: 97%
“…Since vaccination became available, Italian CVID patients, as well as CVID from other countries, were immunized mostly with mRNA COVID-19 vaccines. Four groups have recently reported immune responses to vaccines in patients with inborn errors of immunity, including CVID patients (24)(25)(26)(27). In the study by Hagin et al, 70% of the adult patients with predominantly antibody deficiency developed specific humoral and T-cell responses after 2 doses of SARS-CoV-2 mRNA vaccine.…”
Section: Insight On Sars-cov-2 the Adaptive Immune Responsesmentioning
confidence: 99%
“…Collectively, these reports indicate that APECED patients, particularly adults and/or those with underlying pneumonitis, can be at risk for severe COVID-19. Therefore, APECED patients should be prioritized for vaccination against SARS-CoV-2, which they appear to tolerate without unusual adverse events; however, it is important to note that not all APECED patients develop robust humoral responses to the SARS-CoV-2 vaccine, especially those receiving immunomodulatory therapy ( 103 ). In our experience with SARS-CoV-2–infected APECED patients at the NIH Clinical Center, we proceed with prophylactic hospital admission upon diagnosis for close clinical monitoring.…”
Section: Pathogenesis Of Aire Deficiencymentioning
confidence: 99%
“…3,4 Our patients with CVID have been followed up for more than 6 months since having completed the 2dosage mRNA vaccine schedule, and none of them have developed or had flare-ups of autoimmune or other long-term inflammatory conditions; other studies have reported reassuring safety data as well. 2,5,6 Furthermore, patients with rheumatologic diseases who have a myriad of autoimmune conditions have been thus far safely vaccinated with mRNA vaccines, with no apparent impact on disease activity and no further safety concerns in the short term. 7,8 Severe adverse events, albeit rare, may nonetheless occur after vaccination, regardless of preexisting medical conditions.…”
Section: Authors' Responsementioning
confidence: 99%